Effects of engine variables and heat transfer on the performance of biodiesel fueled IC engines. (April 2015) - Yunus khan, T.M.; Badruddin, Irfan Anjum; Badarudin, Ahmad; Banapurmath, N.R.; Salman Ahmed, N.J.; Quadir, G.A.; Al-Rashed, Abdullah A.A.A.; Khaleed, H.M.T.; Kamangar, Sarfaraz
Abstract: These days internal combustion engines are the major source of transportation. They run mainly on fossil fuels which are depleting day by day not only that they cause pollution which endangers human life and creates environmental problems. Of late biodiesel has emerged as a better alternative fuel for internal combustion engines due to its comparable properties with that of fossil fuels. Today's automobiles require economy of operation, high power output and last but not the least, reduction in greenhouse gases emitted by the vehicles. Such specific demands have compelled the researchers not only to focus on the parameters affecting the performance but also on emission of the internal combustion engines. This paper reviews the effects of different engine variables such as compression ratio, load and speed, fuel injection parameters, air swirl, piston design on the performance of engine. Special attention has been paid on the future automotive engines which would be significantly governed by electronic systems. According to us the same technology can also be employed in analyzing engines running on biofuels.